2011
DOI: 10.21273/hortsci.46.6.908
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Attributes Related to Fruit Size in Pomegranate

Abstract: Pomegranate fruit is valued for its juice-containing arils and is consumed and marketed as whole fresh fruit, extracted arils, juice, syrup (grenadine), wine, teas, seed oil, and other products. Recent consumption has rapidly increased attributable in part to reported health benefits that include efficacy against coronary heart disease, atherosclerosis, cancer, hypertension, and infectious diseases. Within commercial orchards, the size of fruits produced can be quite variable even with trees of the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 29 publications
7
33
3
1
Order By: Relevance
“…Wetzstein et al . () reported that pomegranate seeds are deep red in colour. In general, the darkness of gluten‐free bread was acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…Wetzstein et al . () reported that pomegranate seeds are deep red in colour. In general, the darkness of gluten‐free bread was acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that punicalagin concentration in mesocarp and exocarp is higher than in the arils of the pomegranate fruit (Fig. ) . Therefore, punicalagin concentrations in juices of pomegranates harvested in 2015 were measured using two extraction methods: one for juices extracted from arils and the second for juices extracted from the whole fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Pomegranate ( Punica granatum L.) is a small tree originally from central Asia (Iran, Turkmenistan and northern India), and is one of the oldest cultivated fruits for food, beverage and medicinal uses . Pomegranate trees are currently growing in temperate, subtropical and tropical areas around the world, with a global production of 1 500 000 t .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations